Catalytic Asymmetric Synthesis of Axially Chiral Diaryl Ethers through Enantioselective Desymmetrization - Bao, Hanyang; Chen, Yunrong; Yang, Xiaoyu (Angewandte Chemie International Edition, 2023)
Axially chiral diaryl ethers are a type of unique atropisomers bearing two potential axes, which have potential applications in a variety of research fields. However, the catalytic enantioselective synthesis of these diaryl ether atropisomers is largely underexplored when compared to the catalytic asymmetric synthesis of biaryl or other types of atropisomers. Herein, we report a highly efficient catalytic asymmetric synthesis of diaryl ether atropisomers through an organocatalyzed enantioselective desymmetrization protocol. The chiral phosphoric acid‐catalyzed asymmetric electrophilic aromatic aminations of the symmetrical 1,3‐benzenediamine type substrates afforded a series of diaryl ether atropisomers in excellent yields and enantioselectivities. The facile construction of heterocycles by the utilizations of the 1,2‐benzenediamine moiety in the products provided access to a variety of structurally diverse and novel azaarene‐containing diaryl ether atropisomers. A highly efficient enantioselective desymmetrization protocol is disclosed for the asymmetric synthesis of axially chiral diaryl ethers by using a chiral phosphoric acid‐catalyzed electrophilic aromatic amination. This method features broad substrate scope, high yields and high enantioselectivity. The facile derivatization of various products into a series of structurally novel azaarene‐containing diaryl ether atropisomers was also demonstrated.